Aqueous enzymatic extraction of protein and lipid from the microalgae species Chlamydomonas reinhardtii - Soto Sierra, Laura (Kansas State University, 2016)
Microalgae has potential as a biofuel feedstock and as a source of valuable bioproducts for a variety of food, feed, nutraceutical, and pharmaceutical industries. However, several challenges are associated with bioproduct extraction from microalgae. The complexity of microalgae cell necessitates use of energy intensive disruption methods but current chemical or mechanical techniques can degrade economically valuable bioproducts. Aqueous enzymatic extraction (AEE), is a non-solvent and environmentally friendly bio-product recovery method that provides an opportunity to design an integrated process for protein and oil fractionation while reducing industrial costs. Based on the mechanistic understanding of biomolecule distribution and compartmentation, an aqueous enzymatic treatment for the release of internally stored proteins and lipid bodies in wild type Chlamydomonas reinhardtii was developed. In this study, we optimized harvesting times that maximized lipid and protein yields in nitrogen depleted cultures of the microalgae Chlamydomonas reinhardtii. Furthermore, an aqueous enzymatic extraction (AEE) treatment was developed. First, four lytic enzymes were tested for their ability to permeate C. reinhardtii cell walls. After cells were permeable, another set of enzymes were tested for their ability to release internally stored bioproducts. Protein recovery and lipid characterization after enzymatic treatment indicated a 54% release of total soluble protein and a localization of lipids to the chloroplast. Additionally, the development of secondary enzyme treatment for chloroplast disruption achieved about 70% total lipids released into the supernatant. Taken together, results indicate the application of an enzymatic treatment scheme for protein and oil recovery as a promising alternative to traditional extraction processes.
Keywords: Microalgae; Enzyme; Autolysin; Protein; Lipid; Cell disruption